Impact of Precision Medicine on Clinical Outcomes: A Single-Institution Retrospective Study - Quinn, Ryann; Patel, Rajvi; Sison, Cristina; Singh, Amandeep; Zhu, Xin-Hua (Frontiers in Oncology, 2021)
Introduction: The strategy of precision medicine has been widely adopted in the practice of community oncology, although the efficacy remains unclear. This study assesses clinical outcomes in patients with an actionable alteration through F1CDx testing and who received a targeted therapy based on the results. Materials and Methods: Retrospective cohort study of patients with tumors that underwent F1CDx from September 2012 to July 2018. F1CDx provided actionable alterations for patients to select appropriate therapies. The primary objective was to estimate the objective response rate (ORR) at 3 months from the start of study treatment. The secondary objectives were to estimate progression free survival (PFS) and overall survival (OS). Results: 652 patients were identified as having actionable mutations. 38 patients (18 males and 20 females) received targeted therapy and were included in the study. The most common alterations were PD-1/PDL-1, high-TMB, P13K, and HER2/ERBB2. Patients received various targeted treatments including nivolumab, pembrolizumab, trastuzumab, and everolimus. 8 (23.53%) and 6 (17.65%) patients achieved partial response (PR) and stable disease (SD), respectively; 20 (58.82%) had progression of disease (PD). The disease control rate was 41.1%. The median PFS was 2.73 months and median OS was 9.93 months. Discussion: Our results demonstrate promising data in precision medicine in real community oncology practice. It warrants further large and prospective studies in patients with actionable alterations.